Home visits in the Danish High Risk and Resilience Study – VIA 7: assessment of the home environment of 508 7‐year‐old children born to parents diagnosed with schizophrenia or bipolar disorder. (17th June 2019) - Gantriis, D. L.; Thorup, A. A. E.; Harder, S.; Greve, A. N.; Henriksen, M. T.; Zahle, K. K.; Stadsgaard, H.; Ellersgaard, D.; Burton, B. K.; Christiani, C. J.; Spang, K.; Hemager, N.; et al.
Abstract : Objective: The home environment provided by the caregivers of a child is an influential single factor for development and well‐being. We aimed to compare the quality of the home environment of children at familial high risk of schizophrenia or bipolar disorder with population‐based controls. Methods: Danish nationwide registers were used to retrieve a cohort of 522 7‐year‐old children of parents diagnosed with schizophrenia ( N = 202), bipolar disorder ( N = 120) or none of these diagnoses ( N = 200). The home environment was assessed using the Middle Childhood‐Home Observation for Measurement of the Environment Inventory (MC‐HOME Inventory). Results: The proportion of children living in home environments that were evaluated not to meet the needs of a 7‐year‐old child was significantly larger in the two familial high‐risk groups. This was true for 21% of the children with familial predisposition for schizophrenia and 7% of children with familial disposition for bipolar disorder. Conclusion: Children born to parents diagnosed with schizophrenia and to a lesser extent bipolar disorder are at an increased risk of growing up in a home environment with an insufficient level of stimulation and support. Identifying families with inadequate home environments is a necessary step towards specialized help and support to at‐risk families.